1994
DOI: 10.1210/jcem.78.1.8288705
|View full text |Cite
|
Sign up to set email alerts
|

Local production and action of follistatin in human placenta.

Abstract: The aim of the present study was to investigate the possible production, localization, and action of follistatin in human placenta, fetal membranes (amnion, chorion), and maternal decidua. Four different experimental approaches were used: 1) Southern blot analysis following reverse polymerase chain reaction to identify follistatin messenger RNA (mRNA) in tissue homogenates; 2) immunohistochemistry to localize immunoreactive (ir-) follistatin in the various intrauterine tissues; 3) measurement by RIA of ir-foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 0 publications
2
25
0
Order By: Relevance
“…This is consistent with indirect evidence from immunohistochemical studies of inhibin subunit localisation and expression (Minami et al 1992, Petraglia et al 1993b. Follistatin has been previously localised to the extraplacental membranes and placental syncytiotrophoblast at term by immunofluorescence (Petraglia et al 1994a), and has been identified in placental homogenates by chromatography and immunoassay (de Kretser et al 1994), but its presence in intrauterine tissues has not been previously quantified. While our data indicates that concentrations of follistatin in gestational tissues are lower than those of activin A, it should be noted that our follistatin ELISA is relatively specific for follistatin 288, cross-reacting only 10% with the 315 isoform.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…This is consistent with indirect evidence from immunohistochemical studies of inhibin subunit localisation and expression (Minami et al 1992, Petraglia et al 1993b. Follistatin has been previously localised to the extraplacental membranes and placental syncytiotrophoblast at term by immunofluorescence (Petraglia et al 1994a), and has been identified in placental homogenates by chromatography and immunoassay (de Kretser et al 1994), but its presence in intrauterine tissues has not been previously quantified. While our data indicates that concentrations of follistatin in gestational tissues are lower than those of activin A, it should be noted that our follistatin ELISA is relatively specific for follistatin 288, cross-reacting only 10% with the 315 isoform.…”
Section: Discussionsupporting
confidence: 75%
“…Both activin and inhibin are members of the transforming growth factor superfamily (TGF-) (Massague 1990, de Kretser 1993, while follistatin is unrelated in structure or sequence (Esch et al 1987). Activin and inhibin subunits are synthesised by the human placenta and extraplacental membranes (Petraglia et al 1990, 1994a, Minami et al 1992, de Kretser et al 1994, Loveland et al 1996, Petraglia 1997. The reported rise in activin A and inhibin A in maternal serum that occurs through pregnancy, particularly in late gestation (Petraglia et al 1993a, 1994b, Muttukrishna et al 1995, Knight et al 1996, Wallace et al 1997, Fowler et al 1998, O'Connor et al 1999, is believed to be a consequence of a rise in placental production, although this has not been proven experimentally and supportive evidence is not conclusive (Minami et al 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Ultrastructure studies and immunohistochemistry of umbilical cord have shown that Wharton's Jelly contains microfibrils of collagen V and VI. The greater expression of follistatin in umbilical cord relative to other parts of placenta is unexpected because most follistatin was believed to be synthesized in placental villi and membranes (29). Follistatin is a direct inhibitor of activin and bone morphogenetic proteins (BMPs) that have been shown to regulate differentiation of progenitor cell types, including hematopoietic cells; its expression may have a role in regulating stem cell renewal vs. differentiation in the umbilical cord.…”
Section: Resultsmentioning
confidence: 99%
“…FST can modulate ovarian function by decreasing follicle stimulating hormone (FSH) and thus influencing follicle and corpus luteum development (reviewed by Knight et al 2012). Considerably less is known about the interactions of activin A and FST within the human uterus and fallopian tube, although these proteins are known to have key roles in the process of decidualisation and the establishment of pregnancy (Petraglia et al 1994;Jones et al 2002aJones et al , 2002bTierney and Giudice 2004;Refaat and Ledger 2011). Furthermore, Fst isoform expression changes throughout the oestrous cycle in rats (Mercado et al 1993) and is increased in the uteri of mice during early pregnancy (Craythorn et al 2012).…”
Section: Introductionmentioning
confidence: 99%